The use of the primary structure of the ITS1–ITS2 region for species identification in some submerged aquatic macrophytes of the genus Stuckenia - A. V. Mglinets; О. E. Kosterin (Вавиловский журнал генетики и селекции)
Applicability of ITS1–ITS2 primary structure for species attribution of representatives of the genus Stuckenia was experimentally tested. Analysis of the ITS1–ITS2 region sequences of S. vaginata and S. pectinata from public databases showed that they differed by insertions/deletions and single or double nucleotide substitutions. Besides, the ITS1–ITS2 region of S. pectinata was shown to be represented by two haplotype groups designated as S. pectinata type A and S. pectinata type B with good bootstrap support in phylogenetic reconstructions. In 28 samples identified as S. pectinata, S. vaginata, S. macrocarpa and S. chakassiensis on the basis of morphology, the ITS1–ITS2 region was sequenced in this study. Three groups of samples with good bootstrap support were revealed to be corresponding to S. vaginata, S. pectinata type A and S. pectinata type B. The S. vaginata group was formed by the samples identified on the basis of morphology as S. vaginata, and the S. pectinata type A group was formed by the samples identified on the basis of morphology as S. pectinata. The S. pectinata type B group was further divided into two subgroups, S. pectinata type B subgroup and S. chakassiensis subgroup. The S. chakassiensis subgroup included mainly the samples identified as such on the basis of morphology. The S. pectinata type B subgroup included samples identified on the basis of morphology as S. pectinata, S. vaginata and S. macrocarpa. We suppose that these samples were S. pectinata type B, S. macrocarpa and their hybrids.